INVENTARISASI TUMBUHAN OBAT TRADISIONAL MASYARAKAT KAMPUNG KEBO DISTRIK PANIAI UTARA KABUPATEN PANIAI PROVINSI PAPUA - Elisabeth Payung Allo; Frans Degei; Herlando Sinaga (Jurnal Biogenerasi, 2021)
Medicinal plants are materials derived from plants that are still simple, pure, not mixed or processed, namely plants that can only be picked and mixed, then consumed immediately. This study aims to determine the types, parts (organs) and ways of using plants by the people of Kebo Village, North Paniai District, Paniai Regency, as traditional medicine. This research was conducted in November-December 2018. The method used is descriptive exploratory with observation and interview stages. The results showed that there were 66 types of plants used as traditional medicinal plants. The parts of the plants used are leaves, stems, fruit, skin, sap, roots, tubers and rhizomes, where the leaf parts have a high percentage of use. The technique of compounding traditional medicinal plants is divided into several parts according to the local community, namely pounding, grated, wrapped, boiled, chewed, and squeezed, but some are used directly without mixing.